ANALISIS KEUNTUNGAN PETANI KOPRA DI KECAMATAN TENGAKABUPATEN MINAHASA SELATAN - Christian ., Suherman; Vicky V.J. Palenewen; Arie D.P Mirah (Sam Ratulangi University, 2016)
This study aims to determine whether the business copra in the district Tenga still profitable, to determine what the Break Event Point Tenga copra farmers in the district, and to identify factors - factors that affect business profits copra. The data used are primary and secondary data. Determination of the sample villages in this study using the